Economic Impact of Road Traffic Accident on Patients Attending at National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka - Karim, Mohoshina; Khan, Abdul Wadud; Farah, Shayela (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 45-49 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13560